METHODS OF DETERMINATION OF ENZYMATIC ACTIVITY IN ELYSA - Umarova Tamila Abdufattoevna; Kudratova Zebo Erkinovna; Ibrayimov Azimjon Tolibjon ogli (Web of Journals Publishing, 2024)
The photometric method of recording enzyme activity is the most widely used in ELISA. In this case, enzyme substrates are substances whose transformation products are colored compounds or, conversely, the color of the substrates themselves changes during the reaction. Colored compounds absorb visible light, i.e. electromagnetic radiation with wavelengths of 400-700 nm. Light absorption obeys the Bouguer-Lambert-Bera law, according to which the optical density of a solution in a certain range is directly proportional to the concentration of the substance. A spectrophotometer is used to measure the optical density [3,5].